THE VASCULAR ENDOTHELIUM FUNCTION INDICATORS IN ORAL LIQUID OF IQOS SMOKING ADOLESCENTS - T.M. Popova; O.A. Nakonechna; O.V. Tishchenko; L.S. Kryvenko (Український стоматологічний альманах)
Heated tobacco products (HTP) were introduced to the world market as an alternative to conventional tobacco cigarettes. Active advertising, readily available to purchase and the public's perception that HTP are a safer alternative to conventional tobacco cigarettes lead to increasing their consumption by young age group in Ukraine. Despite the claims by the tobacco corporations about reduction of adverse effects the HTP on the activity of cardiovascular system, the published studies of potential vascular endothelial consequences were not found. Therefore, the aim of our study is to assess the HTP effect on vascular endothelial cells by determination of the nitrate, nitrite, S-nitrosothiols, and endothelin-1 levels in saliva of smoking adolescents. The object and research methods. Thirty adolescents aged 14-17 years old were divided to three groups. Group I was introduced by ten healthy non-smoking adolescents (control group). Group II consists of ten smoking adolescents have smoked the IQOS for two years. Group III is formed by ten smoking adolescents who have smoked the IQOS for three years. The salivary nitrate and nitrite levels were measured using the Griess assay such as an indicator of NO production. The salivary S-nitrosothiols were measured spectrophotometrically. The salivary endothelin-1 level was measured with ELISA kit. Statistical analysis of the data was carried out using the STATISTICA 7.0 program. The data were presented as Median values (Me), lower and upper quartile, i.e. Me [Lq; Uq]. Statistical significance was accepted if p < 0.05. Results. The salivary nitrate concentrations in groups II (Me = 14.11 [13.98; 14.52] μmol/l) and III (Me = 12.06 [11.44; 12.31] μmol/l) were significantly decreased compared to group I (Me = 15.89 [14.98; 16.89] μmol/l, KW test: H = 23.59, p=0.000. The values of nitrite in groups II and III were the following: Me = 2.32 [1.47; 2.48] μmol/l and 1.37 [1.25; 1.44] μmol/l, respectively. The indices were lower in 1.41 and 2.36 times than in group I: Me = 3. 24 [3.05; 3.78] μmol/l, KW test: Н = 22.92, p = 0.000. The levels of salivary S-nitrosothiols in group II are: Me = 1.02 [0.84; 1.27] μmol/l and group III Me = 0.36 [0.25; 0.62] μmol/l were reduced in 1.75 and 4.97 times compared to group I: Me = 1.79 [1.67; 1.97] μmol/l, KW test: Н = 24.46, р = 0.000. We assume that the reduction of salivary nitrate and nitrite concentrations is associated with a low level of S-nitrosothiols which serve as deposited and released nitric oxide (NO). Probably, the decrease of nitrates and nitrites is associated with the inhibition of endothelial NO synthase. The salivary endothelin-1 level was significantly higher in group II: Ме=0.58 [0.53; 0.73] pmol/ml and in group III: Ме = 0.82 [0.79; 0.93] pmol/ml than in group I: Ме = 0.17 [0.14; 0.26] pmol/ml, KW test: Н = 23.94, р = 0.000. It should be noted, the significant differences between data of nitrate, nitrite, S-nitrosothiol and endothelin-1 content in groups II and III were found (Mann-Whitney U test, nitrates - Z = 3.62, p = 0.000; nitrites - Z = 2.91 , p = 0.003; S-nitrosothiols - Z = 3.74, p = 0.00; endothelin-1 - Z = 3.36, p = 0.000). These results showed interrelation between adverse IQOS effect on vascular endothelium of adolescents duration of IQOS smoke. Conclusions. The adverse effect of heated tobacco product (IQOS) on the biochemical indicators of the vascular endothelium function of adolescents was found in our experimental study. The salivary nitrate, nitrite and S-nitrosothiols levels were significantly decreased in IQOS smoking adolescents. The salivary endothelin-1 content was significantly elevated in IQOS smoking adolescents. The revealed changes indicate the endothelial dysfunction in young smokers. The development of pathological processes in the vascular endothelium depends on the smoking duration.